PERSEPSI IBU RUMAH TANGGA TENTANG VOLUNTARRY COUNCELLING AND TESTING (VCT) TERHADAP PERILAKU PENCEGAHAN HIV-AIDS - Khosidah, Amik; Purwanti, Sugi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
The Housewife including one of the groups at risk for HIV / AIDS and according to the survey the housewife is a second ranked as a professional contributor to HIV-AIDS. This is because HIV-AIDS can be transmitted by sexual partners housewife who frequently changing partners. Transmission of HIV-AIDS through their husbands to wives have a significant role in the spread and the increasing prevalence of STIs and HIV / AIDS in Banyumas. The objective of this research is to analyze the factors that influence the behavior of housewives in doing Councelling Voluntary Testing (VCT) for prevention of HIV-AIDS in Puskesmas Baturaden. The method was analytic survey research, with cross sectional approach. The research was a quantitative research and qualitative research using triangulation logic that quantitative research results can be checked with the results of qualitative research, so that both the results of the research are expected to enhance the validity of the conclusions of the research. Quantitative research population was all women of reproduction age some 893 people from two villages in Puskesmas Baturaden. The sample size in this research was the number of women of reproduction age 90. Sampling procedures of quantitative research used stratified sampling method. Samples kualititaif done by purposive sampling with criteria informants who knowing information about VCT. They are a housewife who did VCT with positive and negative outcomes and puskesmasâ€s staff. Keywords: Voluntary Councelling Testing (VCT), Perception, HIV-AIDS